How Does Augmented Reality Contribute to Enhancing Consumer Experience? Comprehending Customer Satisfaction by AR Marketing Media - Muhammad Tata Rizky Setyo Utomo; Tito Wira Eka Suryawijaya; Peter S. Fader (Jurnal Ekonomi dan Bisnis Digital, 2023)
This research aims to investigate the role of Augmented Reality (AR) in improving consumer experiences in the retail sector after the global pandemic through a qualitative approach. Involving in-depth interviews and participant observation, the research found that the use of AR in Optimization Marketing was effective in increasing brand visibility, consumer interaction and sales growth. The level of consumer interactivity with AR also significantly influences positive perceptions of brands and products, forming the basis for the formation of long-term loyalty. The implications of this research show that investment in Optimization Marketing with AR can be a strategic key in improving consumer experience and building loyalty in the post-pandemic retail sector.